2020
DOI: 10.1093/femsre/fuaa043
|View full text |Cite
|
Sign up to set email alerts
|

Host cell death during infection withChlamydia: a double-edged sword

Abstract: The phylum Chlamydiae constitutes a group of obligate intracellular bacteria that infect a remarkably diverse range of host species. Some representatives are significant pathogens of clinical or veterinary importance. For instance, Chlamydia trachomatis is the leading infectious cause of blindness and the most common bacterial agent of sexually transmitted diseases. Chlamydiae are exceptionally dependent on their eukaryotic host cells as a consequence of their developmental biology. At the same time, host cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 239 publications
(308 reference statements)
0
18
0
Order By: Relevance
“…The increased expression of the active phosphorylated forms p-MLKL, p-RIP1 and p-RIP3 after pathogenic infection activates the necroptotic complex necessary to initiate the membrane pore formation in those immune cells to release inflammatory arsenals (DAMPs) necessary to maintain an inflammatory milieu and thereby invite the adaptive response which results in aggravated pathogenicity ( 12 ). These biomarkers were also increased in spleen cell lysates stimulated with other pathogens ( 5 , 17 , 29 , 32 ). The spotty increased expression of those key biomarkers at 24h and 72h post infection with the nonpathogenic L. biflexa suggests a discontinuous inflammatory process as the innate response is enough to provide protection.…”
Section: Discussionmentioning
confidence: 92%
“…The increased expression of the active phosphorylated forms p-MLKL, p-RIP1 and p-RIP3 after pathogenic infection activates the necroptotic complex necessary to initiate the membrane pore formation in those immune cells to release inflammatory arsenals (DAMPs) necessary to maintain an inflammatory milieu and thereby invite the adaptive response which results in aggravated pathogenicity ( 12 ). These biomarkers were also increased in spleen cell lysates stimulated with other pathogens ( 5 , 17 , 29 , 32 ). The spotty increased expression of those key biomarkers at 24h and 72h post infection with the nonpathogenic L. biflexa suggests a discontinuous inflammatory process as the innate response is enough to provide protection.…”
Section: Discussionmentioning
confidence: 92%
“…IFNγ has a role as an immunomodulator produced by natural killer (NK) and T lymphocytes (Farrar & Schreiber, 1993). It has been shown that the presence of IFNγ in cells infected by Chlamydia can halt the developmental cycle of Chlamydia , resulting in a persistent infection (Perfettini et al, 2003; Sixt, 2021). IFNγ is required for activation of the antibody‐mediated response to Chlamydia infection (Hafner & Timms, 2018; Naglak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Others played a role in lymphocyte differentiation (PATZ1), the cellular response to stress (RAD51AP1) and leukocyte migration (HSD3B7), while LAAO‐like had no GO term associations. Of the 17 genes, only three have previously been associated with disease caused by Chlamydia infection in other species (TLR5, STAT2 and IFNγ) (Beckett et al, 2012; Derbigny et al, 2005; Hosey et al, 2015; Perfettini et al, 2003; Sixt, 2021). We also identified two MHC Class I genes associated with disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, many intracellular bacterial species have evolved ways of inhibiting cell death signaling; nevertheless, bacterial induction of cell death during infection remains prevalent (Lamkanfi & Dixit, 2010). For instance, Chlamydia species have been shown to be capable of inhibiting host cell death during early and mid‐stages of infection and inducing death at later stages, allowing for pathogen dissemination (Sixt, 2021). Chlamydia can also induce death in neighboring cells, which may prevent activation of an immune response by depleting immune cells (Sixt, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chlamydia species have been shown to be capable of inhibiting host cell death during early and mid‐stages of infection and inducing death at later stages, allowing for pathogen dissemination (Sixt, 2021). Chlamydia can also induce death in neighboring cells, which may prevent activation of an immune response by depleting immune cells (Sixt, 2021). With regard to C. burnetii , apoptosis plays an important role in infection, as do autophagy and pyroptosis (Cordsmeier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%